37PPlasma ctDNA RAS mutation analysis by digital polymerase chain reaction in patients with inoperable pancreatic cancer. (7th November 2019) - Gkoura, S; Kastrisiou, M; Kougioumtzi, A; Tzallas, C; Gkrepi, K; Goussia, A; Magklara, A; Pentheroudakis, G
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is associated with poor prognosis and high mortality worldwide. Despite the emergence of new therapeutic approaches for the treatment of inoperable PDAC, reliable prognostic/predictive biomarkers are lacking. PDAC harbours mutations in the KRAS gene in 80-90% of patients. The aim of the present study is the detection and quantification of RAS mutations in the ctDNA of patients with inoperable PDAC by BEAMing digital polymerase chain reaction (PCR), in order to (a) evaluate the correlation with tissue RAS mutation status in the tumour, (b) study the baseline prognostic significance and (c) study the predictive significance of ctDNA RAS mutation kinetics for the prediction of response to systemic/neoadjuvant therapy. Methods: Plasma samples of patients with locally advanced or metastatic inoperable PDAC were collected at diagnosis and at 4-6 weeks after treatment initiation and were tested for 34 mutations in the KRAS and NRAS genes by BEAMing digital polymerase chain reaction (PCR). This method has a particularly high sensitivity and can accurately quantify mutated DNA as the Mutant Allele Fraction (MAF). To test the efficacy and validity of ctDNA for the detection of RAS mutations, RAS mutations will also be tested for on paired tumour tissue samples of the patients under study by PCR. Results: So far, 38 plasma samples from 20 patients were available for analysis. At baseline, mutant ctDNA pertaining to exon 2 codon 12 of the KRAS gene was detected in all patients' samples and, additionally, to exon 3 codon 61 of the NRAS gene in one of them. Comparison of plasma and tissue results revealed a high agreement of the RAS mutational profile in plasma ctDNA and tissue tumour DNA. Kinetics of the RAS mutational load during therapy and its prognostic or predictive value will be analysed with further cohort expansion. Conclusions: This work highlights the potential role of liquid biopsies in the management of PDAC and, more specifically, will yield preliminary data on the role of RAS ctDNA profiling as a predictive and prognostic marker. Legal entity responsible for the study: Department of Medical Oncology, University General Hospital of Ioannina. Funding: Hellenic Society of Medical Oncology (HeSMO) and Society for Study of Clonal Heterogeneity of Neoplasia (EMEKEN). Disclosure: G. Pentheroudakis: Research grant / Funding (institution), Support material was provided for this project: Sysmex Inostics. All other authors have declared no conflicts of interest.